Inovação e criatividade nas pequenas e médias empresas - Girardi, Luiz Tadeu de Azevedo (2002)
The importance of small and medium enterprises for the economy of a country is fundamental because they have several strategic social and economic roles. Besides contributing to the production of national wealth, they also counterbalance the vulnerabilities of large companies providing the necessary economic balance. Socially their contribution is directly related to the lessening of unemployment, functioning also as source of stability in the community, as a means of reducing inequalities in the distribution of income among regions and economic groups, and contributes, decisively, to limit migration to urbans area. The capacity to innovate is now a key component for the survival and development of small organizations. The future today is increasingly less predictable using past parameters and the business world is more turbulent. The objective of this is to point out the need to revise the models which serve as examples for their adoption of competitive alternatives of development and to offer theoretical-practical knowledge to make possible the implementation of the innovative culture in small enterprises. It emphasizes, moreover, that in the present context, flexibility and skills to work in ambiguous situations and to find creative solutions become central concerns of businessmen and managers.